Analyzing research methods on sexual violence in Colombia's internal armed conflict (2014)
In order to do an accurate legal research on sexual violence in the context of armed conflict it is essential to determine the appropriate methodologies to identify and understand this phenomenon. Since the 2000s, national and international NGOs and activists have approached sexual violence in the context of the Colombian internal armed conflict through the documentation of specific cases and the identification of relevant national and international laws. The Colombian Constitutional Court followed suit, and in 2008 issued Writ 092 (Auto 092) using that very same methodology. In 2009, Consultoría para los Derechos Humanos y el Desplazamiento (CODHES) applied a new methodology to study sexual violence in armed conflict context using the category of analysis 'massacre'. After testing the usefulness of that category of analysis in three continuous researches, it was evident that this new category also has conceptual downsides. This article elaborates on those disadvantages and proposes a new category to analyze sexual violence in the context of the Colombian armed conflict: Giorgio Agamben's theorisations of the camp.